The Moderating Role of Risk Committee on the Corporate Risk Disclosure-Firm Value Relationship - Lydia Ulimazni Vivolanda; Nurna Aziza; Saiful Saiful (Jurnal Dinamika Akuntansi dan Bisnis, 2026)
This study examines the relationship between Corporate Risk Disclosure (CRD) and firm value (MVA), with the Risk Committee as a moderating variable. Using a sample of 182 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024, the data were analyzed using multiple regression and Moderated Regression Analysis (MRA). The results reveal that CRD has a positive impact on firm value, suggesting that transparent risk communication enhances investor confidence. Furthermore, the Risk Committee strengthens this relationship, acting as a vital contingent factor. Theoretically, this study contributes to Contingency Theory by demonstrating that the value relevance of risk disclosure is maximized under robust governance oversight. The novelty lies in identifying the Risk Committee as a 'contextual enabler' that transforms risk information into credible market signals within the manufacturing sector.